Toxoplasma gondii Infection and Clinical Characteristics of Patients With Schizophrenia: A Systematic Review and Meta-analysis. Issue 1 (26th August 2020) - Sutterland, Arjen L; Mounir, David A; Ribbens, Juul J; Kuiper, Bouke; van Gool, Tom; de Haan, Lieuwe
Abstract: Schizophrenia is associated with an increased prevalence of IgG antibodies against Toxoplasma gondii ( T. gondii seropositivity), whereby the infection seems to precede the disorder. However, it remains unclear whether a T. gondii infection affects clinical characteristics of schizophrenia. Therefore, a systematic review and meta-analysis was conducted following PRISMA guidelines examining the association between T. gondii seropositivity and severity of total, positive, or negative symptoms or age of onset in schizophrenia. PubMed, Embase, and PsycInfo were systematically searched up to June 23, 2019 (PROSPERO #CRD42018087766). Random-effects models were used for analysis. Furthermore, the influence of potential moderators was analyzed. Indications for publication bias were examined. From a total of 934 reports, 13 studies were included. No overall effect on severity of total, positive, or negative symptoms was found. However, in patients with a shorter duration of illness T. gondii seropositivity was associated with more severe positive symptoms (standardized mean difference [SMD] = 0.32; P < .001). Similar but smaller effects were seen for total symptoms, while it was absent for negative symptoms. Additionally, a significantly higher age of onset was found in those with T. gondii seropositivity (1.8 y, P = .015), although this last finding was probably influenced by publication bias and study quality. Taken together, these findings indicate that T. gondii infection has a modest effect on the severity of positive and total symptoms in schizophrenia among those in the early stages of the disorder. This supports the hypothesis that T. gondii infection is causally related to schizophrenia, although more research remains necessary.